Investment in Malaysia: forecasting stock market using time series analysis / Nuzlinda Abdul Rahman ... [et al.] - Abdul Rahman, Nuzlinda; Chen, Yi Kit; Pang, Kevin; Shaik Abdullah, Fauhatuz Zahroh; Izani, Nur Sofiah (2021)
Investment is the asset committed to generate additional income. Investing is often described as the process of laying out money for now in the expectation of gaining more money in the future. Every investment comes with a different magnitude of risk. This study aims to investigate the performance of the Kuala Lumpur Composite Index (KLCI) from 1997 to 2018, to forecast the value of KLCI stock market for the coming three years and to investigate whether investment in stock market is the best in terms of profit for the coming three years. The ARIMA model approach was applied to study the KLCI time series. Model building and diagnostic checking techniques were conducted to determine a statistically adequate model. Result indicate that the stock market is highly volatile. For an investor which is willing to take high risk, investment on KLCI stock market will be the suitable choice.